An incremental approach for building accessible and usable web applications - Medina Medina, Nuria; Burella, Juan; Rossi, Gustavo Héctor; Grigera, Julián; Robles Luna, Esteban (2010)
Building accessible Web applications is difficult, moreover considering the fact that they are constantly evolving. To make matters more critical, an application which conforms to the well-known W3C accessibility standards is not necessarily usable for handicapped persons. In fact, the user experience, when accessing a complex Web application, using for example screen readers, tends to be far from friendly. In this paper we present an approach to safely transform Web applications into usable and accessible ones. The approach is based on an adaptation of the well-known software refactoring technique. We show how to apply accessibility refactorings to improve usability in accessible applications, and how to make the process of obtaining this "new" application cost-effective, by adapting an agile development process.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Web Information Systems Engineering - WISE 2010 : 11th International Conference, Hong Kong, China, December 12-14, 2010. Proceedings. Berlín : Springer, 2010. (Lecture Notes in Computer Science ; 6488), pp. 564-577
Keywords: ACCESIBILIDAD WEB; PERSONAS CON DISCAPACIDADES; REQUERIMIENTOS